Influence Unemployment and Education Against Poverty in the District Brebes 2008-2022 - Hilda Firdaus; Ila Navilah; Anton Sudrajat (Cirebon International Journal of Economics and Business, 2024)
Standing a country basically is For well-being for all over people or its inhabitants , however problem base For reach That that is poverty . Poverty level in the District Brebes Alone Still spelled out high , up to enter to extreme poor category mainly in the Province Central Java . For That need done various effort For lower poverty in the District Brebes . Therefore​ That objective from study This is For know and analyze Influence Unemployment and Education towards Poverty in the District Brebes . In study this , researcher use method study quantitative and data used using secondary data with method documentation . Research techniques in study This is an analysis technique multiple linear regression , and subjects in research This that is Regency Brebes in 2008 – 2022. Results from study This in a way Partial Unemployment showing that mark significance as big as 0.482 > 0.05 and value t count -0.725 > t table - 2.178 meaning Unemployment to Poverty in a way Partial No have significant influence .​ Then mark significance in Education towards Poverty is mark significance of 0.000 > 0.05 and value t count - 8.082 < t table - 2.178 meaning between Education and Poverty in a way Partial have negative and significant influence .​ However , in fact simultaneous obtained mark significance 0.000 and value f count (31,801) > value f table (3,885). With thereby can stated that variable Unemployment and Education Together have influence significant to poverty in the District Brebes in 2008 – 2022.